IMPORTANT IMPORTANCE AND SOLUTIONS OF MAPPING AREAS OF HIGH TECHNOGENIC RISK IN SOUTHWESTERN UZBEKISTAN - Pulatov Asliddin Sayfullayevich (Web of Journals Publishing, 2025)
This article examines the methods of identifying and mapping zones of high technogenic risk in the southwestern regions of Uzbekistan, their problems and significance. These zones have arisen as a result of the rapid development of industry, exploitation of natural resources and environmental degradation, posing a serious threat to infrastructure, agriculture and human life. The study uses modern geoinformation technologies - GIS (geographic information systems), satellite imagery, drone (UAV) data and spatial modeling tools to identify risk zones, analyze their ecological footprints and integrate this data into the state cadastral system. The proposed methodological approach serves to make scientifically based decisions on environmental management and emergency risk reduction.
Keywords: Technogenic risk, GIS, drone mapping, satellite imagery, spatial analysis, digital cadastral system, Uzbekistan.